Teacher's creativity in making video based learning in post pandemi covid-19 - Meirza Nanda Faradita; Kunti Dian Ayu Afiani; Ade Firmannandya (Jurnal Bidang Pendidikan Dasar, 2023)
Education in the post-covid-19 pandemic takes place in a hybrid manner. Offline and online learning methods using certain platforms such as zoom meeting and google classroom. The problems that arise in online learning such as students' boredom in learning, this is because the methods and media in online learning are still not varied. This study aims to analyze the creativity of teachers in making learning video media for class IV SD in the post-covid-19 pandemic. The research method uses descriptive qualitative. Data collection techniques used interviews with principals and teachers, and observation. The subject in this study was the online learning video media applied by the teacher. The object in this study is the teacher's creativity in making video based learning. The results of this study, teachers can be said to be creative because they can create video-based learning media, so that students are active in participating in learning.